2021
DOI: 10.3390/molecules26123485
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water Hardness on Catechin and Caffeine Content in Green Tea Infusions

Abstract: The health benefits of green tea are associated with its high catechin content. In scientific studies, green tea is often prepared with deionized water. However, casual consumers will simply use their local tap water, which differs in alkalinity and mineral content depending on the region. To assess the effect of water hardness on catechin and caffeine content, green tea infusions were prepared with synthetic freshwater in five different hardness levels, a sodium bicarbonate solution, a mineral salt solution, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…[ 21 ] in which pH of tea infusions decreased significantly (p < 0.05) after brewing with hard alkaline water. This indicated that the brewing process had an effect of lowering the pH value of tea infusion [ 6 ]; Xu et al. , 2017) that might be due to the extraction of compounds in the tea leaves such as organic acids, phenols, carboxylic groups, and amino acids.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 21 ] in which pH of tea infusions decreased significantly (p < 0.05) after brewing with hard alkaline water. This indicated that the brewing process had an effect of lowering the pH value of tea infusion [ 6 ]; Xu et al. , 2017) that might be due to the extraction of compounds in the tea leaves such as organic acids, phenols, carboxylic groups, and amino acids.…”
Section: Resultsmentioning
confidence: 99%
“…reported that interaction between catechins and water components and caused the flavour profile of the infusions to be affected by the water composition. The use of tap water for tea preparation is the most common method used by casual tea consumers [ 6 ]. However, the sensory preferences for tap water infused tea were inconsistent which might be due to the variation of water composition of tap water in different regions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theaflavins are present in smaller amount in fermented teas [23]. Caffeine is another characteristic component of tea and is present in considerable amount, almost regardless of the kind of tea [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…However, EGCG bioavailability shows high interindividual variability related to gastrointestinal absorption, stability of the molecule, nutritional environment, and administration conditions. It is important to note that green tea catechins are more stable at low temperatures and acidic pH conditions [ 20 , 21 , 22 ]. An in vitro study showed that EGCG catechins prevented influenza virus replication by blocking hemagglutinin (HA) in the adsorption phase [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%